2009
DOI: 10.1002/ejic.200900710
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium(II) Complexes of the dpp‐BIAN Radical‐Anion: Synthesis, Molecular Structure, and Catalytic Activity in Lactide Polymerization

Abstract: Reaction of (dpp-BIAN)Mg(THF) 3 (1) {dpp-BIAN = 1,2-bis [(2,6-diisopropylphenyl)imino]acenaphthene} with one molar equivalent of 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO) proceeds with oxidation of the dpp-BIAN dianion in 1 to the radical-anion and affords the (dpp-BIAN)-Mg(TEMPO)(thf) (2) complex. The reaction of dpp-BIAN with an excess amount of magnesium and 0.5 molar equivalents of I 2 in Et 2 O gives (dpp-BIAN)MgI(Et 2 O) n , which then reacts in situ with (Me 3 Si) 2 NK to produce (dpp-BIAN)-Mg[N(SiMe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(42 citation statements)
references
References 78 publications
(41 reference statements)
3
39
0
Order By: Relevance
“…Details of the synthesis, characterization data and the crystallographic protocols employed in this study are given in the Supporting Information. CCDC 990851 (3), 990852 (6), 990853 (7) contain the supplementary crystallographic data for this paper. These data can be obtained free of charge from The Cambridge Crystallographic Data Centre via www.ccdc.cam.ac.uk/data_request/cif.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Details of the synthesis, characterization data and the crystallographic protocols employed in this study are given in the Supporting Information. CCDC 990851 (3), 990852 (6), 990853 (7) contain the supplementary crystallographic data for this paper. These data can be obtained free of charge from The Cambridge Crystallographic Data Centre via www.ccdc.cam.ac.uk/data_request/cif.…”
Section: Methodsmentioning
confidence: 99%
“…[1] Much of this attention has centered on its utility in polymer synthesis, [2] organic oxidation reactions [3] and, due to its persistent radical character, in molecular magnetism. [4] Although the use of TEMPO as a radical donor ligand is dominated by reports of redox-active d-block complexes, [5] there is also more limited precedent for the use of TEMPO in d 0 f- [6] and s-block [7] complex chemistry. Mulvey and co-workers reported the first Group 1 and 2 complexes of TEMPO in 2001, [7a] noting not only its coordination as a neutral two electron donor but also its ability to adopt an anionic electron configuration when ligating Group 2 cations in complexes of the form [{(Me 3 Si) 2 N}Mg{m-TEMPO}] 2 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of such very high rates, excellent polymerization control, tolerance to low loadings, and high isoselectivity is very rare and noteworthy (106). Mg complexes with diamide ligand such as 34 promote isotactic polymerization of rac-lactide to afford stereoblock copolymer, although P m is not clear (107).…”
Section: Polymerization Of Lactidesmentioning
confidence: 99%
“…Recently, we demonstrated that the chelate ene‐bisamide form of the ligand dpp‐bian (=1,2‐bis[(2,6‐diisopropylphenyl)imino]acenaphthene) readily stabilizes the d 0 configuration of the titanium atom with the formation of the chlorido complex [(dpp‐bian)TiCl 2 ] 2 , which appears to be an easy‐to‐use precursor for further dpp‐bian‐supported titanium derivatives. It should be noted that magnesium and calcium complexes of dpp‐bian have proved to be robust catalysts for the ROP of L ‐ and rac ‐lactides, forming PLAs which are non‐toxic toward human fibroblasts, while the binuclear aluminum compound [(dpp‐bian)Al] 2 was found to be an extremely active initiator of the controlled ROP of ε‐caprolactone at room temperature . In an effort to expand the scope of non‐toxic catalytic systems based on dpp‐bian for the polymerization of cyclic esters, we report on the synthesis and catalytic activity of titanium alcoholates stabilized with dianionic and radical anionic forms of dpp‐bian, in the ROP of L‐lactide (LA) .…”
Section: Introductionmentioning
confidence: 99%